Amniotic growth factors enhanced human pre‐adipocyte cell viability and differentiation under hypoxia. Issue 9 (6th April 2022) - Magana, Alejandro; Giovanni, Regina; Essien, Edidiong; Epel, Boris; Kotecha, Mrignayani; Liu, Songyun; Mathew, Mathew T.; Hagarty, Sarah E.; Bijukumar, Divya
Abstract: One of the major drawbacks associated with autologous fat grafting is unpredictable graft retention. Various efforts to improve the survivability of these cells have been explored, but these methods are time‐consuming, complex, and demand significant technical skill. In our study, we examine the use of cryopreserved amniotic membrane as a source of exogenous growth factors to improve adipocyte survivability under normal and hypoxic conditions. Human primary preadipocytes were cultured in a gelatin‐ferulic acid (Gtn‐FA) hydrogel with variable oxygen concentration and treated with amniotic membrane‐derived condition medium (CM) for 7 days. This hydrogel provides a hypoxic environment and also creates a 3D cell culture to better mimic recipient site conditions. The O2 concentration in the hydrogel was measured by electron paramagnetic resonance oxygen imaging (EPROI). The conjugation of FA was confirmed by FTIR and NMR spectroscopy. The cell viability and adipocyte differentiation were analyzed by alamarBlue™ assay, Oil Red O staining, and RT‐qPCR. The expression of genes: Pref‐1, C/EBP β, C/EBP α, PPAR‐ƴ, SLC2A4, and VEGF‐A were quantified. The cell viability results show that the 50% CM showed significantly higher cell pre‐adipocyte cell viability. In addition, compared to normal conditions, hypoxia/CM provided higher PPAR‐ƴ ( p < .05), SLC2A4, and VEGF‐A ( p < .05) (early and terminal differentiating markers) mRNA expression. This finding demonstrates the efficacy of amniotic CM supplementation as a novel way to promote adipocyte survival and retention via the expression of key gene markers for differentiation and angiogenesis.